FRI0089 Utility of a Novel Inflammatory Marker, Glyca, for Assessment of Rheumatoid Arthritis Disease Activity and Coronary Atherosclerosis. (9th June 2015) - Ormseth, M.; Chung, C.; Oeser, A.; Connelly, M.; Sokka, T.; Raggi, P.; Solus, J.; Otvos, J.; Stein, C.M.
Abstract : Background: GlycA is a novel inflammatory biomarker measured using nuclear magnetic resonance (NMR). Its NMR signal primarily represents glycosylated acute phase proteins. GlycA is associated with inflammation and development of cardiovascular disease in initially healthy women. We hypothesized that GlycA is a biomarker of disease activity and is associated with coronary artery atherosclerosis in patients with rheumatoid arthritis (RA). Methods: We conducted a cross-sectional study of 166 patients with RA and 90 control subjects. GlycA was measured from an NMR signal originating from N-acetylglucosamine residues on circulating glycoproteins. The relationship between GlycA and RA disease activity (DAS28 score) and coronary artery calcium score was determined. Results: GlycA concentrations were higher in patients with RA (median [interquartile range]: 398 μmol/L [348, 473 μmol/L]) than control subjects (344 μmol/L [314, 403 μmol/L], P<0.001). In RA, GlycA was strongly correlated with DAS28-ESR and DAS28-CRP and their components including tender and swollen joint count, global health score, ESR and CRP (All P<0.001). The area under the receiver operating characteristic curve for GlycA's ability to differentiate between patients with low versus moderate-to-high disease activity based on DAS28-CRP was 0.75 (95% CI: 0.68, 0.83). For each quartile increase in GlycA, odds of having coronary artery calcium increased by 48% (95% CI: 4%, 111%), independent of age, race and sex (P=0.03). Conclusions: GlycA is a novel inflammatory marker that may be useful for assessment of disease activity and is associated with coronary artery atherosclerosis in patients with RA. Disclosure of Interest: M. Ormseth: None declared, C. Chung: None declared, A. Oeser: None declared, M. Connelly Employee of: LabCorp, T. Sokka: None declared, P. Raggi: None declared, J. Solus: None declared, J. Otvos Employee of: LabCorp, C. M. Stein: None declared